The Effect of Phytocannabinoids and Endocannabinoids on Nrf2 Activity in the Central Nervous System and Periphery - Pietro Marini; Mauro Maccarrone; Luciano Saso; Paolo Tucci (Neurology International, 2024)
The relationship between nuclear factor erythroid 2-related factor 2 (Nrf2) and phytocannabinoids/endocannabinoids (pCBs/eCBs) has been investigated in a variety of models of peripheral illnesses, with little clarification on their interaction within the central nervous system (CNS). In this context, evidence suggests that the Nrf2-pCBs/eCBS interaction is relevant in modulating peroxidation processes and the antioxidant system. Nrf2, one of the regulators of cellular redox homeostasis, appears to have a protective role toward damaging insults to neurons and glia by enhancing those genes involved in the regulation of homeostatic processes. Specifically in microglia and macroglia cells, Nrf2 can be activated, and its signaling pathway modulated, by both pCBs and eCBs. However, the precise effects of pCBs and eCBs on the Nrf2 signaling pathway are not completely elucidated yet, making their potential clinical employment still not fully understood.